Analisis Faktor – Faktor yang Berperan dalam Penguatan Kinerja Pegawai di Badan Penanggulangan Bencana Daerah (BPBD) Kota Langsa - Risud Alfrando Sagala; Suri Amilia; Dhian Rosalina (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to determine the effect of training, compensation, and work facilities on employee performance at the Regional Disaster Management Agency (BPBD) of Langsa City. The approach used in this research is quantitative, with a population of 156 employees. The sample determination in this study is a random sampling technique, and the calculation uses the Slovin formula with an error rate of 5% (0.05), so that the number of respondents in this study is 112 people. The data analysis method used is multiple linear regression, t test for partial analysis, F test for simultaneous analysis, and the coefficient of determination test (Adjusted R²). So from the results of multiple linear regression, the equation Y = 10.491 + 0.247X₁ + 0.275X₂ + 0.255X₃ is obtained. Thus, based on the t-test results, it shows that training has a significant value (t sig.) of 0.000 < 0.05, compensation of 0.001 < 0.05, and work facilities of 0.012 < 0.05. This result indicates that training, compensation, and work facilities significantly affect employee performance at BPBD Langsa City. Furthermore, the F test results show a significant value (F sig.) of 0.000 < 0.05, which explains that training, compensation, and work facilities simultaneously significantly influence employee performance. The coefficient of determination test (Adjusted R²) produces a value of 0.336, which indicates that the variables of training, compensation, and work facilities affect employee performance by 33.6%. The remaining 66.4% is influenced by other variables not included in this study, such as occupational safety and health (OHS), work stress, work experience, competence, workload, job satisfaction, work culture, work discipline and external organisational factors.